A new approach to credit ratings - Pertaia, Giorgi; Prokhorov, Artem; Uryasev, Stan (Journal of Banking & Finance, 2022)
Credit ratings are fundamental in assessing the credit risk of a security or debtor. The failure of the Collateralized Debt Obligation (CDO) ratings during the financial crisis of 2007-2008 and the massive undervaluation of corporate risk leading up to the crisis resulted in a review of rating approaches. Yet the fundamental metric that guides the construction of credit ratings has not changed. We study the inadequacies of the old metric in simple models of investment and in structured finance portfolio optimization tasks, and we propose a new methodology based on a buffered probability of exceedance. The new approach offers a conservative risk assessment, with substantial conceptual and computational benefits. We illustrate the new approach using several examples and report the results of a structuring step-up CDO case study, with details available in an online Supplement.